Some Results for Generalized Suzuki Type Z-Contraction in θ−Metric Spaces: Plern Saipara, Poom Kumam, Pheerachate Bunpatcharacharoen - Team, Support (Thai Journal of Mathematics, 2018)
The purpose of this paper, we introduce the concept of Suzukitype Z-contraction and prove the existence of fixed point results for this contraction in theta metric spaces. As an application, we apply our result to showthe solvability of nonlinear Hammerstein integral equations.